Darfur : a 21st century genocide - Prunier, Gérard (Crises in world politics., 2008)
Examines the political, economic, and cultural factors that led to the 2004 Darfur crisis in Western Sudan, during which Arab Janjaweed militias engaged in a campaign of violence against the residents of Western Sudan.